13th InterSociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems 2012
DOI: 10.1109/itherm.2012.6231498
|View full text |Cite
|
Sign up to set email alerts
|

Development and analysis of a compact cooling system using the microcompressor

Abstract: For electronics cooling, the matching between size and efficiency is a desirable aspect of the design of cooling units. Hence, the compact cooling units are suitable for this area of refrigeration due to high capacity by size ratio and lightweight. For this purpose, Embraco developed a new refrigerating system for small enclosures and command panels with the use of a new miniaturized linear compressor called microcompressor. This unit consists in an outdoor mounted air-conditioning with finned-tube heat exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Detailed numerical models have been developed and validated to improve the design and therefore the performance of these compressors [86,87], as well as experimental tests [55], where a constant-speed, oil-free linear compressor was used for electronics cooling in aeronautical applications, in which the mass flow and cooling capacity were controlled by varying the piston stroke. This same micro compressor was presented by Ribeiro [54]. It is a hermetic linear compressor with cylindrical form and 60 mm in diameter and 160 mm in length that weighs 1.3 kg.…”
Section: Compressorsmentioning
confidence: 98%
See 2 more Smart Citations
“…Detailed numerical models have been developed and validated to improve the design and therefore the performance of these compressors [86,87], as well as experimental tests [55], where a constant-speed, oil-free linear compressor was used for electronics cooling in aeronautical applications, in which the mass flow and cooling capacity were controlled by varying the piston stroke. This same micro compressor was presented by Ribeiro [54]. It is a hermetic linear compressor with cylindrical form and 60 mm in diameter and 160 mm in length that weighs 1.3 kg.…”
Section: Compressorsmentioning
confidence: 98%
“…The need for compact telecom cooling units that may perform as efficient substitutes for thermoelectric coolers and the scarcity of studies in the literature motivated Ribeiro to test a VCR system for this application. The initial work [53] presented a prototype made of a linear oil-free micro compressor, finned tube heat exchangers as condenser and evaporator, and a capillary tube as an expansion device, operating with R134a. The overall dimensions were 528 × 127 × 96 mm 3 and 3.1 kg weight, and it used 59 g of optimized refrigerant mass and a 1.10 m long capillary with 0.518 mm diameter.…”
Section: Electronics Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Henceforth, by utilizing silica gel, water tank is not required and also silica gel absorbs moisture so that it will also reduce the weight of cooler and helps to maintain a hygienic environment. In the paper [2], the technology developed in the paper, "Development and analysis of compact cooling system" involves a commercially available thermoelectric system used for electronics cooling was also tested and compared with the vapor compression system. The results have shown that the micro compressor unit presented a coefficient of performance (COP) approximately two times larger than thermoelectric solution and higher cooling capacities were achieved under low ambient temperatures.…”
Section: Literature Surveymentioning
confidence: 99%
“…So, we have defined our problem statement as "LAYMAN'S AIR COOLER". As it is probably one solution which not only is cheaper as an appliance, but also uses lower power than conventional air conditioners [2]. In big cities, the problem is associated with the space and high installation cost of cooling appliances.…”
Section: Problem Statementmentioning
confidence: 99%